2008
DOI: 10.2151/jmsj.86.415
|View full text |Cite
|
Sign up to set email alerts
|

Precursory Changes in Planetary Wave Activity for Midwinter Surface Pressure Anomalies over the Arctic

Abstract: The development of surface pressure anomalies observed in January over the Arctic is investigated based on composite analysis of observed data. The monthly anomalies in January with a high degree of zonal symmetry are found to extend from the surface into the lower stratosphere, in a manner similar to the Arctic Oscillation (AO). The formation of the AO-like signature in January tends to follow the strengthening/weakening of upward propagation of planetary waves in November over the western portion of Eurasia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
6
13
0
Order By: Relevance
“…Previous studies (e.g. Takaya and Nakamura, 2008; Nishii et al , 2011) suggested that an anticyclonic circulation over the B‐K Seas in late autumn and early winter affects the midwinter stratospheric circulation, weakening the intensity of the westerly zonal wind. As documented by Deser et al (2007), in midwinter the linear and nonlinear responses to sea‐ice reduction interact destructively, resulting in a zero near‐surface anomaly.…”
Section: Results From the Sensitivity Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (e.g. Takaya and Nakamura, 2008; Nishii et al , 2011) suggested that an anticyclonic circulation over the B‐K Seas in late autumn and early winter affects the midwinter stratospheric circulation, weakening the intensity of the westerly zonal wind. As documented by Deser et al (2007), in midwinter the linear and nonlinear responses to sea‐ice reduction interact destructively, resulting in a zero near‐surface anomaly.…”
Section: Results From the Sensitivity Experimentsmentioning
confidence: 99%
“…The modified wave pattern consists of an intensified dipole of zonally asymmetric temperatures whose net effect is a stronger warm advection into the pole. This finding is consistent with the results of Takaya and Nakamura (2008). Kim et al (2014) and Sun et al (2015) also found that the upper‐level intensified heat flux associated with sea‐ice reduction in the Barents and Kara Seas was explained by modifications of a large‐wavenumber Z pattern in the upper troposphere.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also suggested stratospheric influence as a possible mechanism for the teleconnection between the variations in tropical SST and the NAO [ Scaife et al ., ; Cagnazzo and Manzini , ]. Takaya and Nakamura [] pointed out the importance of fluctuations of planetary waves in November to the annular mode in mid‐winter through modulation of the stratospheric polar vortex. It is thus not unrealistic to consider a possible link between sea‐ice reduction and the negative phase shift of the NAO in late winter via the stratospheric pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The anomaly reached the surface within a week, suggesting a downward coupling that might have contributed to the building of the subsequent major episode B3 that in turn amplified the sea ice deficit over the BKS. The above findings are consistent with Takaya and Nakamura () and Peings (), who showed that UB activity in November acts to increase the upward flux of planetary waves and thereby weaken the stratospheric vortex in December into January.…”
Section: Troposphere‐stratosphere Couplingmentioning
confidence: 99%